Regional Sustainable Development – Czech Region Ranking UsingMulti-criteria Decision Analysis - Hudrlikova, Lenka; Petkovova, Ludmila (European Journal of Sustainable Development, 2013)
The aim of the paper is to provide a ranking of the Czech NUTS 3 regions based onsustainable development indicators. The original list of indicators was published by theCzech Statistical Office in 2008 and reviewedin 2010. In the analysis the same set ofindicators with the latest data was used. The indicators in each pillar are merged by meansof linear aggregation withweights derived from the principal component analysis.Because three pillars of sustainable development (environmental, economic and social)are assumed to be non-compensable, the multiple-criteria decision analysis is applied on apillar level in the final composite indicator. Both two main approaches – Borda andCondorcet were considered. Since the Borda approach leads to the compensability of theindicators, the Condorcet approach was in the spotlight. Advancedrules and adjustmentfor Condorcet approach were employed. Advantages and disadvantages of the methodsare provided. As a result more final rankings exist. The deep discussion about the resultsis provided. The special attention is paid to the capital city Prague, border regions, andindustrial regions. In addition, the correlation between final ranking and other indicatorsis tested.